Institutional Ownership and Discretionary Accruals: Empirical Evidences from Pakistani Listed Non-Financial Companies - Shaikh, Abdul Mateen; ., Syed Zulfiqar Ali Shah (Information Management and Business Review, 2012)
Current study empirically investigates the impact of institutional ownership on discretionary accruals; we took a sample size of 68 listed non -financial companies from a population of 652 companies listed on Karachi Stock Exchange (KSE). This data was gathered for the period of 5 years, starting from 2006 up to 2010. Modified Jones Model was employed for this study to quantify discretionary accruals while institutional ownership measured by dividing number of shares kept by institutions from total number of shares outstanding. The fix effect model showed that the magnitude of discretionary accruals in Pakistani listed firms tends to significantly decrease for the firms where institutions hold a decent amount of share of that particular firm. Thus the findings of this study are in consensus with our hypothesis, which proposes that institutional ownership is quite an effective tool in aligning insider management and administration to take the right decision for value maximizing of the companies, and thus shareholders.